TARIAN RITUAL, PESTA KOLEKTIF, DAN KONSERVASI LINGKUNGAN DALAM UPACARA MANGANAN DI BLORA - Budi Setiyono (Gelar : Jurnal Seni Budaya, 2009)
What today we call as  traditional arts, is often a form of ritual in the past  or part of it. A form of ritual is not only a human  activity to make a relation to transcendental being, but also as a way to create a balance and sustainable life. Based on Roy Rappaport’s thought, stating that rituals are modes of communication which transfers the  practical information of physiological, psychological and sociological condition of a certain group, the study attempts  to explain the rationalization of dancing and fertility ritual manganan in Blora in functionalism perspective. To Blora community, manganan ritual and buoh tradition that to be at its peak on tayuban performances are social and symbolic ways to perpetuate the natural as well as economic, and also to maintain  their  social resource  Key words : ritual, conservation, social resource, natural recourse